2006
DOI: 10.2341/05-18
|View full text |Cite
|
Sign up to set email alerts
|

Creep as a Mechanism for Sealing Amalgams

Abstract: SUMMARY INTRODUCTIONMicroleakage in dentistry has been studied for more than 50 years (Buchanan, 1951;Massler & Ostrovsky, 1954). Through the use of varied techniques and different test media, such as dyes and radioactive materials, microleakage is one of the most widely studied phenomena (Cochran & others, 2004). Kidd (1976) defined microleakage as the passage of bacteria, fluids, molecules or ions along the interface of a dental restoration and wall of the cavity preparation. Hilton (2002a,b) reports that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[11][12][13][14][15] The limited protective properties of current restoratives underscore the significant challenge that secondary caries still presents as a failure mode for restorative materials. Notwithstanding the long-standing observation that dental amalgam occludes marginal defects by either deposition of metallic corrosion products and/or material creep mechanisms; 16,17 no other currently available direct or indirect dental material has demonstrated an analogous ability to seal or reseal marginal defects. 18 Clearly, additional functionalities added to dental restorative materials could augment fluoride release to improve longevity of dental restorations, especially by improving long-term marginal stability of dental restorations.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The limited protective properties of current restoratives underscore the significant challenge that secondary caries still presents as a failure mode for restorative materials. Notwithstanding the long-standing observation that dental amalgam occludes marginal defects by either deposition of metallic corrosion products and/or material creep mechanisms; 16,17 no other currently available direct or indirect dental material has demonstrated an analogous ability to seal or reseal marginal defects. 18 Clearly, additional functionalities added to dental restorative materials could augment fluoride release to improve longevity of dental restorations, especially by improving long-term marginal stability of dental restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Amalgam alloy show reduce in the microleakage overtime, this reduction has been explained by corrosion products filling the interface gap in order to seal the restoration. (20) Amalgam restoration is still the best material used for amalgam repair even without bonding material. From clinical point, repair cause less damage than complete replacement of amalgam and it is therefore preferred.…”
Section: Discussionmentioning
confidence: 99%
“…In 1983, Lin demonstrated that low-copper amalgam had a greater potential for corrosion-ultimately reducing microleakage along the restorative interface [107] [108]. However, due to an almost phenomenological hyperbole regarding mercury toxicity & the rapid emergence of glass ionomers & adhesive restorations since the 1970's, caused a decline in amalgam placement.…”
Section: The Cavosurface Margin: It Leaksmentioning
confidence: 99%